A combined laboratory and numerical study of heat transport by baroclinic eddies and axisymmetric flows - Read, P (2003)
The effective contribution to the lateral heat transport in a rotating differentially heated annulus attributable to fully developed baroclinic eddies is determined by the combined use of laboratory measurements and numerical simulations. The total heat transport is determined in the laboratory by real-time calorimetry to a precision of around ±2.5% over a wide range of parameters sampling a wide cross-section of the regular baroclinic wave regime accessible in the rotating annulus up to the transition to geostrophic turbulence. High-resolution numerical simulations of steady axisymmetric flow in the rotating annulus were carried out under comparable parametric conditions to the laboratory experiments, to determine the contribution to total heat transport due to the axisymmetric boundary-layer circulation in the system. The difference between the Nusselt or Péclet numbers determined in these two ways enables the heat transport attributable to the presence of the baroclinic eddies to be determined unambiguously. The variation of the resulting excess Péclet number with external parameters appears to be consistent with predictions from a weakly nonlinear model of baroclinic instability within the regular baroclinic wave regime, at least for weak-moderate supercriticality, whereas at higher rotation rates a parametrization based on the linear instability approach of Green (1970) may be more appropriate. This approach seems to offer an accurate and incisive means of evaluating schemes proposed to parametrize the transport properties of baroclinic eddies in a variety of models used in geophysical and engineering applications.